The Pitch invader-COVID-19 cancelled the game: What can science do for us, and what can the pandemic do for science? - Bok, D.; Chamari, K.; Foster, C. (International Journal of Sports Physiology and Performance, 2020)
This was supposed to be a great year for athletes, coaches, sports scientists, and fans. The 4-year Olympic cycle was completing its final stages, and the Tokyo 2020 Olympic Games were on the horizon. UEFA Euro 2020 should have taken us through 12 countries to determine the new European soccer champion in mid-July. Before that, we were supposed to enjoy numerous sporting events across the globe yielding new champions in different sports and competition levels. And then, COVID-19 hit. On March 11, 2020, the World Health Organization declared a pandemic caused by novel coronavirus (COVID-19), triggering unprecedented postponement/cancellation of sporting events around the globe, including the summer Olympic Games. Just as in the final minutes of a game a naked "streaker," a "pitch invader," runs across the field with security personnel in pursuit, causing the game to be disrupted and bringing frustration and misery to our faces, COVID-19 brought sport, and much more in daily human life, to a halt.